2004
DOI: 10.1016/s0002-9394(03)01416-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification and localization of major soluble vitreous proteins in human ocular tissue*1

Abstract: We present a normal human vitreous protein profile using current technologies and provide a baseline for comparison to ocular disease states. Tissue distribution of vitreous proteins may help to elucidate more specific protein function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…All types of crystallins found in this study were significantly lower in the vitreous humour from PDR patients compared with that from the control subjects, and a previous study has reported that beta-crystallin B2 was identified by MALDI-TOF in normal vitreous [12]. We do not know why the crystallin levels are decreased in the vitreous of diabetic patients with PDR; the biological functions of crystallins are not completely understood.…”
Section: Discussioncontrasting
confidence: 59%
“…All types of crystallins found in this study were significantly lower in the vitreous humour from PDR patients compared with that from the control subjects, and a previous study has reported that beta-crystallin B2 was identified by MALDI-TOF in normal vitreous [12]. We do not know why the crystallin levels are decreased in the vitreous of diabetic patients with PDR; the biological functions of crystallins are not completely understood.…”
Section: Discussioncontrasting
confidence: 59%